Perceptions and Practices in School Social Worker-Teacher Interprofessional Collaboration - Stacy A Gherardi; Kimberly Knox; Allison Stoner; Bethany Garling-Spychala (International Journal of School Social Work, 2022)
School social work requires significant skills for interprofessional collaboration, especially collaboration with teachers. While the value of such skills is increasingly recognized in fields such as healthcare, there has been limited attention to assessing or supporting interprofessional practice in education. This exploratory mixed-methods study analyzed survey data from 264 school social workers across the United States in order to understand their perceptions of teachers as collaborators and their practices relating to collaboration with teachers. Barriers to collaboration were also identified. Data suggested that school social workers had positive perceptions of teachers as collaborators generally, but saw limitations in the training and support of teachers to effectively respond to non-academic concerns; time and support for collaboration were identified as significant barriers to collaborative practice.
Keywords: school social work; interprofessional collaboration; interprofessional practice teachers